Mechanical properties of zirconia, doped and undoped yttria-stabilized cubic zirconia from first-principles. (November 2018) - Cousland, G.P.; Cui, X.Y.; Smith, A.E.; Stampfl, A.P.J.; Stampfl, C.M.
Abstract: Density functional theory calculations investigate the mechanical properties of: cubic ( c ), tetragonal ( t ) and monoclinic ( m ) zirconia (ZrO2 ); cubic yttria-stabilized zirconia ( c -YSZ); c -YSZ doped with TiO2, MnO2, CaO and NiO. These find the elastic constants, elastic compliances, bulk, shear and Young's modulus for the three phases of zirconia together with the ideal strength of c -ZrO2 . The ideal strength of c -ZrO2 for strain in the [ 100 ] direction (84.3 GPa) being significantly higher than in the [ 110 ] (30.5 GPa) and [ 111 ] directions (9.87 GPa) is attributed to change in the bond angle reducing the internal strain on the bonds. Adding Y2 O3 to c -ZrO2 decreases the ideal strength, particularly in the [100] direction, namely to respectively 11.1 and 28.8 GPa for 6.67 and 14.29 mol % Y2 O3 . Doping c -YSZ with TiO2, MnO2, CaO and NiO further reduces the ideal strength, with the lowest values for TiO2 (7.16–7.88 GPa). The significant decrease in the ideal strength of c -YSZ and doped c -YSZ compared to c -ZrO2 in the [100] direction is attributed to the weakening of the ZrO2 framework by the oxygen vacancies. Highlights: DFT calculates the mechanical properties of zirconia and stabilized zirconia. DFT calculates elastic constants and compliances, bulk, shear and Young's modulus. For cubic zirconia the greatest calculated ideal strength is in the [100] direction. DFT calculations indicate that the inclusion of yttria decreases ideal strength. Doping with Ti, Mn, Ca and Ni oxides further reduces the calculated ideal strength.